PLC Based Load Sharing of Transformers - Iqra Rana; Murtaza Ali; Faheem Shafeeque Channar; Munsif Ali; Mustafa Memon (NAROTAMA UNIVERSITY, 2020)
The transformer is very expensive and bulky power system equipment. It runs and feed the load for 24 hours a day. Sometimes the load on the transformer unexpectedly rises above its rated capacity in that situation the load on the transformer increases and it will be overloaded and current will increase and cause overheating which in results damage the insulation of transformer. That insulation failure resulting in interruption of power supply. The common problems which transformer face is overloading voltage fluctuations and heating effect. It takes lot of time to fix the transformer so that a device need to be introduced a device which would help in automatically sharing of these over voltages. We will try to build an automated transformer sharing system in this project where the transformer current is confined to auxiliary transformer and automatically enters system. There are three transformers working as sources in this project, initially when the main switched ON the load that time load will be shared through the first transformer but when the load on first transformer suddenly increase above its reference value then immediately second transformer connected parallel with first transformer automatically through PLC by busing relay circuit.